Nitrogen Export From a Watershed Subjected to Partial Salvage Logging - Maria Herrmann; William E. Sharpe; David R. DeWalle; Bryan R. Swistock (The Scientific World Journal)
Logging has been shown to induce nitrogen (N) leaching. We hypothesized that logging a watershed that previously exhibited forest decline symptoms would place additional stress on the ecosystem and result in greater N loss, compared to harvesting vigorous forests. We conducted a 10-year (1988 to 1998) assessment of N export from the Baldwin Creek watershed in southwestern Pennsylvania that was partially clearcut to salvage dead and dying northern red oak. N export from the watershed increased significantly following salvage logging operations and did not completely return to prelogging levels by the end of the study period. The largest annual NO3-N export of 13 kg/ha was observed during the first year after harvesting, an increase of approximately 10 kg/ha. Compared to data from other Appalachian Mountain watersheds in North Carolina, West Virginia, and Pennsylvania, calculated N loss for Baldwin Creek was considerably greater. Longer periods of reduced N uptake due to slow revegetation of salvage logged areas, coupled with increased amounts of N available to leaching, could have accounted for the large N losses observed for Baldwin Creek. Salvage logging of dead and dying trees from forested watersheds in this region appears to have the potential to result in much larger N losses than previously reported for harvest of healthy stands.